A Strong Dose-Response Relation Between Serum Concentrations of Persistent Organic Pollutants and Diabetes - Lee, Duk-Hee; Lee, In-Kyu; Song, Kyungeun; Steffes, Michael; Toscano, William; Baker, Beth A.; Jacobs, David R. (Diabetes care, 2006)
A Strong Dose-Response Relation Between Serum Concentrations of Persistent Organic Pollutants and Diabetes Results from the National Health and Examination Survey 1999–2002 Duk-Hee Lee , MD, PHD 1 , In-Kyu Lee , MD, PHD 2 , Kyungeun Song , MD, PHD 3 , Michael Steffes , MD, PHD 4 , William Toscano , PHD 5 , Beth A. Baker , MD, PHD 5 6 and David R. Jacobs, Jr , PHD 7 8 1 Department of Preventive Medicine and Health Promotion Research Center, School of Medicine, Kyungpook National University, Daegu, Korea 2 Department of Endocrinology, School of Medicine, Kyungpook National University, Daegu, Korea 3 Department of Clinical Pathology, School of Medicine, Kyungpook National University, Daegu, Korea 4 Department of Laboratory Medicine and Pathology, University of Minnesota, Minneapolis, Minnesota 5 Division of Environmental Health Sciences, School of Public Health, University of Minnesota, Minneapolis, Minnesota 6 Regions Hospital, Occupational and Environmental Medicine, St. Paul, Minnesota 7 Division of Epidemiology, School of Public Health, University of Minnesota, Minneapolis, Minnesota 8 Department of Nutrition, University of Oslo, Oslo, Norway Address correspondence and reprint requests to Duk-Hee Lee, MD, PhD, Department of Preventive Medicine, School of Medicine, Kyungpook University, 101 Dongin-dong, Jung-gu, Daegu, Korea 700-422. E-mail: lee_dhatknu.ac.kr Abstract OBJECTIVE —Low-level exposure to some persistent organic pollutants (POPs) has recently become a focus because of their possible link with the risk of diabetes. RESEARCH DESIGN AND METHODS —Cross-sectional associations of the serum concentrations of POPs with diabetes prevalence were investigated in 2,016 adult participants in the National Health and Nutrition Examination Survey 1999–2002. Six POPs (2,2′,4,4′,5,5′-hexachlorobiphenyl, 1,2,3,4,6,7,8-heptachlorodibenzo- p -dioxin, 1,2,3,4,6,7,8,9-octachlorodibenzo- p -dioxin, oxychlordane, p,p ′-dichlorodiphenyltrichloroethane, and trans -nonachlor) were selected, because they were detectable in ≥80% of participants. RESULTS —Compared with subjects with serum concentrations below the limit of detection, after adjustment for age, sex, race and ethnicity, poverty income ratio, BMI, and waist circumference, diabetes prevalence was strongly positively associated with lipid-adjusted serum concentrations of all six POPs. When the participants were classified according to the sum of category numbers of the six POPs, adjusted odds ratios were 1.0, 14.0, 14.7, 38.3, and 37.7 ( P for trend < 0.001). The association was consistent in stratified analyses and stronger in younger participants, Mexican Americans, and obese individuals. CONCLUSIONS —There were striking dose-response relations between serum concentrations of six selected POPs and the prevalence of diabetes. The strong graded association could offer a compelling challenge to future epidemiologic and toxicological research. AhR, aryl hydrocarbon receptor DDE, p,p′-dichlorodiphenyltrichloroethane HCB, hexachlorobenzene HpCDD, 1,2,3,4,6,7,8-heptachlorodibenzo-p-dioxin LOD, limit of detection NHANES, National Health and Nutrition Examination Survey OCDD, 1,2,3,4,6,7,8,9-octachlorodibenzo-p-dioxin PCB, polychlorinated biphenyl PCB153, 2,2′,4,4′,5,5′-hexachlorobiphenyl PCDD, polychlorinated dibenzo-p-dioxin PCDF, polychlorinated dibenzofuran POP, persistent organic pollutant SUMPOP, sum of POP levels TCDD, 2,3,7,8-tetrachlorodibenzo-p-dioxin TEF, toxic equivalency factor Footnotes A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “ advertisement ” in accordance with 18 U.S.C Section 1734 solely to indicate this fact. Accepted April 5, 2006. Received March 10, 2006. DIABETES CARE